2014
DOI: 10.1007/s13277-014-2596-3
|View full text |Cite
|
Sign up to set email alerts
|

miR-204-5p expression in colorectal cancer: an autophagy-associated gene

Abstract: MicroRNAs (miRNAs) are important factors during tumorigenesis by affecting posttranscriptional gene expression. miRNA 204 (miR-204) is a miRNA frequently investigated in different types of cancers. According to literature, autophagy has dual roles in cancer, acting as both a tumor suppressor and cell survival agent. Also, the current data suggests that autophagy is activated in human colorectal cancer cells and enhances the aggressiveness of human colorectal cancer cells. So, our aim is to investigate potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Therefore, these two pathways might have cross-talk, and be regulated by the same miRNA. For example, miR-204 shows both an anti-apoptosis effect and autophagy inhibitory effect155, 156. Up or down regulation of miR-204 may change the transition of apoptosis and autophagy; subsequently, influence chemosensitivity.…”
Section: Aberrant Expression Of Mirnas and Cancer Drug Resistancementioning
confidence: 99%
“…Therefore, these two pathways might have cross-talk, and be regulated by the same miRNA. For example, miR-204 shows both an anti-apoptosis effect and autophagy inhibitory effect155, 156. Up or down regulation of miR-204 may change the transition of apoptosis and autophagy; subsequently, influence chemosensitivity.…”
Section: Aberrant Expression Of Mirnas and Cancer Drug Resistancementioning
confidence: 99%
“…miR‐204‐5p can promote or suppress cancer progression; however, its role in HCC is not clear. In the present study, the expression and role of miR‐204‐5p in HCC will be studied.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Yin et al26 reported that miR-204-5p can inhibit cell survival and accelerate the impact of CT in colorectal cancer. However, these results were contradicted by Sümbül et al,27 who reported significantly higher levels of miR-204-5p in colorectal cancer than in a healthy group. In the latter study, it was suggested that the increased expression of miR-204-5p in colorectal cancers acted to overcome cellular autophagy by inhibiting the expression of LC3B-II and Bcl-2 .…”
Section: Discussionmentioning
confidence: 80%